The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1016/j.paid.2020.110396
|View full text |Cite
|
Sign up to set email alerts
|

“Do I have enough food?” How need for cognitive closure and gender impact stockpiling and food waste during the COVID-19 pandemic: A cross-national study in India and the United States of America

Abstract: Food waste is considered to be one of the biggest issues affecting individuals around the globe. The COVID-19 pandemic, with the consequent lockdown processes, has recently triggered individuals to stockpile foodstuffs. Recent data shows, however, that individuals have not consumed a good proportion of the stockpiled food, resulting in increasing amounts of products ending up wasted. Using a cross-national survey conducted in the United States and India, we investigate how individuals' levels of need for cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
3
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 29 publications
(31 reference statements)
1
65
3
3
Order By: Relevance
“…In the present study, food stockpiling was identified as a significant predictor of increased food waste during the COVID-19 pandemic even after controlling for household and food purchaser characteristics. Food stockpiling during the COVID-19 pandemic has been shown to be associated with the need for a sense of stability and predictability during uncertain times, leading to the adoption of an individualistic strategy associated with buying more even if it leads to food waste or reduced availability of food for others [33]. This finding has important implications regarding food policy, crisis communication, and food purchasing habits, providing an important target for educational interventions with the aim of decreasing food waste and increasing food security during crisis situations.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, food stockpiling was identified as a significant predictor of increased food waste during the COVID-19 pandemic even after controlling for household and food purchaser characteristics. Food stockpiling during the COVID-19 pandemic has been shown to be associated with the need for a sense of stability and predictability during uncertain times, leading to the adoption of an individualistic strategy associated with buying more even if it leads to food waste or reduced availability of food for others [33]. This finding has important implications regarding food policy, crisis communication, and food purchasing habits, providing an important target for educational interventions with the aim of decreasing food waste and increasing food security during crisis situations.…”
Section: Discussionmentioning
confidence: 99%
“…During the early days of the COVID-19 pandemic, there was a fear among the general public about food scarcity. As a result, people started stockpiling food products [14]. However, it was not the case in rural areas.…”
Section: Covid-19 Impact On Rural Households' Food Consumptionmentioning
confidence: 99%
“…Mental rigidity was also related to reduced risk taking in various domains (Schumpe et al, 2017). A study conducted in the US during the COVID-19 pandemic reviled that anxiety related behavior patterns (e.g., stockpiling food) of mentally rigid people were greatly affected in such times of crisis (Brizi and Biraglia, 2020).…”
Section: Mental Rigidity and Stressful Eventsmentioning
confidence: 99%